2008
DOI: 10.1007/s00425-008-0704-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest regulated gene expression and splicing efficiency in storage roots of sugar beet (Beta vulgaris L.)

Abstract: Sixteen post-harvest upregulated genes from sugar beet comprising five novel sequences were isolated by subtractive cloning. Transcription profiles covering a period of up to 49 days after harvest under controlled storage conditions and in field clamps are reported. Post-harvest induced genes are involved in wound response, pathogen defense, dehydration stress, and detoxification of reactive oxygen species. An early induction of a cationic peroxidase indicates a response to post-harvest damage. Wound response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…It was shown that temperature-dependent alternative splicing of OsbZIP58 affects grain filling of rice [ 93 ]. In sugar beet, Bvnpcg2 and Bvnpcg3 are subjected to temperature-dependent alternative splicing, resulting in regulation of the sensitivity to seasonal temperature changes [ 94 ]. In Medicago, temperature-dependent alternative splicing of MtJMJC5, a jumonj C domain-containing demethylase homologue, is involved in the circadian clock [ 95 ].…”
Section: Regulation Of Gene Expression By Temperature-dependent Almentioning
confidence: 99%
“…It was shown that temperature-dependent alternative splicing of OsbZIP58 affects grain filling of rice [ 93 ]. In sugar beet, Bvnpcg2 and Bvnpcg3 are subjected to temperature-dependent alternative splicing, resulting in regulation of the sensitivity to seasonal temperature changes [ 94 ]. In Medicago, temperature-dependent alternative splicing of MtJMJC5, a jumonj C domain-containing demethylase homologue, is involved in the circadian clock [ 95 ].…”
Section: Regulation Of Gene Expression By Temperature-dependent Almentioning
confidence: 99%
“…Recent biotechnological improvements using transformation technologies for sugar beet include salt tolerance and the delay of bolting time (Liu et al 2008; Mutasa-Gottgens et al 2009). Furthermore, tissue specific and storage induced genes and their promoters were identified (Kloos et al 2002; Oltmanns et al 2006; Rotthues et al 2008; Stahl et al 2004). These may be applicable for the spatial and temporal expression of genes to achieve desired biotechnological improvements.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that ten GLP genes classified into two distinguishable clades in a phylogenetic tree have been described from bryophyte, a moss used as a model organism for studies on plant evolution, development, and physiology (Nakata et al 2004). Additionally, at least 9, 7, 6, and 5 GLP genes were isolated from maize (Alexandrov et al 2009), grape (Godfrey et al 2007), sugar beet (Rotthues et al 2008), and pea (Gucciardo et al 2007), respectively.…”
mentioning
confidence: 99%